تحليل محتوى تدريبات مهارة القراءة في كتاب اللغة العربية للسنة الرابعة والخامسة في المدارس الثانوية الماليزية في ضوء تصنيف بلوم المعرفي = Analysis of the content of reading skill exercises in the Arabic language textbook for the fourth and fifth year in Malaysian secondary schools in the light of Bloom's cognitive classification - Ali, Asem Shehadeh Saleh; Alsaidi, Maher; Majahar, Faizah (University of Dhaka, 2022)
يتكون التدريس في الفصل من ثلاثة عناصر رئيسة: المعلم والطالب والكتاب المدرسي الذي يقدم المناهج الدراسية، وفي تقويم محتوى القراءة في كتب اللغة العربية بالمدارس الماليزية تسعى الدراسة إلى الكشف عن النسبة المئوية من تدريبات مهارة القراءة لمستويات تصنيف بلوم المعرفة في كتاب اللغة العربية للسنة الرابعة والخامسة للمستوى الثانوي بالمدارس الماليزية الحكومية، والبحث عن النسبة المئوية من تدريبات مهارة القراءة التي تقع في مستويات التفكير الدنيا والعليا، ومعرفة أوجه الاتفاق والاختلاف بين تدريبات مهارة القراءة في كتاب اللغة العربية من وجهة نظر تصنيف بلوم المعرفي. اتبعت الدراسة المنهج التحليلي المقارن. توصلت الدراسة إلى بعض النتائج، ومنها: اتضح من النتائج أن معظم الأسئلة في تدريبات مهارة القراءة في كتاب اللغة العربية للسنة الرابعة جاءت من مستوى الفهم في تصنيف بلوم المعرفي، وتليها مستوى التذكر، وبالنسبة إلى أسئلة مهارة القراءة في كتاب اللغة العربية للسنة الخامسة، أغلبها تقع في مستوى التذكر، ومستوى الفهم، وتشير النتائج إلى أن نسبة مستويات التفكير الدنيا (التذكر، والفهم، والتطبيق، غلبت على مستويات التفكير العليا (التحليل، والتقويم، والإبداع) بنسبة عالية، وتبين من النتائج أن الأسئلة في تدريبات مهارة القراءة في كتاب السنة الرابعة والخامسة معظمها تستخدم ضمير المتكلم، وقلة قليلة منها تستخدم ضمير المخاطب. ولوحظت أن شكل غالبية الأسئلة وأسلوبها متقاربة مع بعضها البعض، وهذا الأمر يمكن النظر إليه في الأسئلة لكل مستويات بلوم المعرفي، من مستوى التذكر إلى مستوى التقويم. Teaching in the classroom consists of three main components: the teacher, the student, and the textbook that presents the curricula, and in evaluating the reading content in Arabic language books in Malaysian schools, the study seeks to reveal the percentage of reading skill exercises for the levels of Bloom’s knowledge classification in the Arabic language textbook for the fourth and fifth year for the secondary level in Malaysian public schools, and searching for the percentage of reading skill exercises that fall at the lower and higher levels of thinking, and knowing the points of agreement and differences between the reading skill exercises in the Arabic language book from the point of view of Bloom’s cognitive classification. The study followed the comparative analytical method. The study reached some results, including: It became clear from the results that most of the questions in the reading skill exercises in the Arabic language book for the fourth year came from the level of understanding in Bloom’s cognitive classification, followed by the level of remembering, and for the reading skill questions in the Arabic language book for the fifth year, most of them It is located in the level of remembering and the level of understanding, and the results indicate that the percentage of lower levels of thinking (remembering, understanding, and application) prevailed over higher levels of thinking (analysis, evaluation, and creativity) at a high rate. The fourth and fifth most of them use the first person, and very few of them use the second person. It was noted that the form and style of most of the questions are close to each other, and this matter can be seen in the questions for all levels of Bloom's knowledge, from the level of remembering to the level of evaluation.